2008
DOI: 10.1017/s0954579408000278
|View full text |Cite
|
Sign up to set email alerts
|

Emotional difficulties in early adolescence following severe early deprivation: Findings from the English and Romanian adoptees study

Abstract: The study assessed conduct and emotional difficulties in a group of Romanian adoptees at age 11, and serves as a follow-up to assessments made when the children were 6 years old. It was found that there was a significant increase in emotional difficulties, but not conduct problems, for the Romanian sample since age 6. It was also found that emotional difficulty was significantly more prevalent at age 11 in the Romanian group than in a within-UK adoptee group. Emotional difficulties in the Romanian adoptee grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
119
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 54 publications
(79 reference statements)
9
119
1
4
Order By: Relevance
“…It is conceivable that a decline in the risk associated with early adversities occurred only prior to the age of 10 years and not in the age span covered by our study. This would be compatible with the catch-up found in a study of Romanian children adopted into the UK which were followed-up till the age of 11 years (Colvert et al 2008;Rutter et al 2001). However, improvements in that study were seen in specific areas only, for example height, growth, cognitive level and atypical behavior.…”
Section: Trajectories Of Psychiatric Problems In Maltreated Childrensupporting
confidence: 85%
See 3 more Smart Citations
“…It is conceivable that a decline in the risk associated with early adversities occurred only prior to the age of 10 years and not in the age span covered by our study. This would be compatible with the catch-up found in a study of Romanian children adopted into the UK which were followed-up till the age of 11 years (Colvert et al 2008;Rutter et al 2001). However, improvements in that study were seen in specific areas only, for example height, growth, cognitive level and atypical behavior.…”
Section: Trajectories Of Psychiatric Problems In Maltreated Childrensupporting
confidence: 85%
“…On the other hand, the results of the present study are not compatible with some other studies on childhood adversities. In late childhood, emotional and behavioral disturbances were not clearly associated with early deprivation, in a group of early institutionalized Romanian adoptees (Colvert et al 2008;Kreppner et al 2007;Rutter et al 2001). Possibly, the children in this study were too young to measure particular sequelae.…”
Section: Trajectories Of Psychiatric Problems In Maltreated Childrenmentioning
confidence: 65%
See 2 more Smart Citations
“…9 For example, the English Romanian Adoption (ERA) Study observed a significant increase in emotional problems from age 6 to age 11 in previously institutionalized children. 11 An analysis of the National Epidemiologic Survey on Alcohol and Related Conditions compared adopted with nonadopted individuals and found that adoptees had increased odds of developing a mood disorder, anxiety disorder, major depressive disorder, and generalized anxiety disorder. 12 Studies in internationally adopted children showed sleep problems as a main adjustment difficulty, even in the absence of developmental problems.…”
mentioning
confidence: 99%